ACUM, an easily underdiagnosed cause of dysmenorrhea—A case report - Qicai Hu; Qicai Hu; Qicai Hu; Chunlei Guo; Chunlei Guo; Chunlei Guo; Qing Chen; Qing Chen; Qing Chen; Wei Zhang; Wei Zhang; Wei Zhang; et al. (Frontiers in Medicine, 2024)
This report described three cases with long-term severe dysmenorrhea, and these cases were referred to our department for medical help. The diagnosis of accessory cavitated uterine malformation (ACUM) was considered based on symptoms and ultrasound/MRI findings. Moreover, a combined approach involving hysteroscopic surgery and laparoscopic surgery was undertaken, and no complications occurred during surgery and in the post-operative period. It is important to consider ACUM in patients with severe dysmenorrhea that does not respond to medical management. Surgery is the most effective treatment for this anomaly.